Novel mutations in penicillin-binding protein genes in clinical Staphylococcus aureus isolates that are methicillin resistant on susceptibility testing, but lack the mec gene - Ba, Xiaoliang (Oxford University Press, 2014)
OBJECTIVES: Methicillin-resistant Staphylococcus aureus (MRSA) is an important global health problem. MRSA resistance to β-lactam antibiotics is mediated by the mecA or mecC genes, which encode an alternative penicillin-binding protein (PBP) 2a that has a low affinity to β-lactam antibiotics. Detection of mec genes or PBP2a is regarded as the gold standard for the diagnosis of MRSA. We identified four MRSA isolates that lacked mecA or mecC genes, but were still phenotypically resistant to pencillinase-resistant β-lactam antibiotics. METHODS: The four human S. aureus isolates were investigated by whole genome sequencing and a range of phenotypic assays. RESULTS: We identified a number of amino acid substitutions present in the endogenous PBPs 1, 2 and 3 that were found in the resistant isolates but were absent in closely related susceptible isolates and which may be the basis of resistance. Of particular interest are three identical amino acid substitutions in PBPs 1, 2 and 3, occurring independently in isolates from at least two separate multilocus sequence types. Two different non-conservative substitutions were also present in the same amino acid of PBP1 in two isolates from two different sequence types. CONCLUSIONS: This work suggests that phenotypically resistant MRSA could be misdiagnosed using molecular methods alone and provides evidence of alternative mechanisms for β-lactam resistance in MRSA that may need to be considered by diagnostic laboratories.